Novel synthetic opioids - toxicological aspects and analysis - Inês Tabarra; Sofia Soares; Tiago Rosado; Joana Gonçalves; Ângelo Luís; Sara Malaca; Mário Barroso; Thomas Keller; José Restolho; Eugenia Gallardo (Oxford University Press, 2019)
Over the past few years, there has been an emerging number of new psychoactive drugs. These drugs are frequently mentioned as "legal highs", "herbal highs", "bath salts" and "research chemicals". They are mostly sold and advertised on online forums and on the dark web. The emerging new psychoactive substances are designed to mimic the effects of psychoactive groups, which are often abused drugs. Novel synthetic opioids are a new trend in this context and represent an alarming threat to public health. Given the wide number of fatalities related to these compounds reported within the last few years, it is an important task to accurately identify these compounds in biologic matrices in order to administer an effective treatment and reverse the respiratory depression caused by opioid related substances. Clinicians dealing with fentanyl intoxication cases should consider that it could, in fact, be a fentanyl analogue. For this reason, it is a helpful recommendation to include synthetic opioids in the routine toxicological screening procedures, including analysis in alternative matrices, if available, to investigate poly-drug use and possible tolerance to opioids. To address this public health problem, better international collaboration, effective legislation, effective investigation, control of suspicious "research chemicals" online forums and continuous community alertness are required. This article aims to review diverse reported fatalities associated with new synthetic opioids describing them in terms of pharmacology, metabolism, posology, available forms, as well as their toxic effects, highlighting the sample procedures and analytical techniques available for their detection and quantification in biological matrices.